Dilema Cucu sebagai Ahli Waris: Perbandingan Hukum Mesir dan Indonesia - Muhibbussabry; M. Iqbal Irham; Faisar Ananda; Dhiauddin Tanjung (Al-fiqh, 2026)
This article analyzes the differences between the legal constructions of Egypt and Indonesia in addressing the dilemma of grandchildren whose parents predeceased the decedent, thereby potentially causing them to be excluded by closer heirs. The study focuses on a comparison between the obligatory bequest (waṣiyyah wājibah) in Egyptian law and substitute heirs in Indonesian law. This research employs a normative juridical method using statutory, conceptual, comparative-law, and maqāṣid al-sharī‘ah approaches. The findings show that Egypt, through Law of Bequest No. 71 of 1946 (Qanun al-Wasiyyah), provides protection for grandchildren through a bequest limited to a maximum of one-third of the estate. In contrast, Indonesia, through Article 185 of the Compilation of Islamic Law, positions grandchildren as substitute heirs who receive a share based on the position of the parent they replace. The findings of this article affirm that the difference between the two systems is not merely a technical matter of inheritance distribution, but reflects different paradigms in the reform of Islamic inheritance law: Egypt adopts a protective-testamentary model, while Indonesia adopts a representative-inheritance model. From the perspective of maqāṣid al-sharī‘ah, both models are oriented toward the protection of lineage and property, but they differ in balancing legal certainty, the protection of grandchildren, and justice for other heirs.